Smart farming adoption – a scoping review - Zhahir, Amirul Asyraf; M. Shuhud, Mohd Ilias; Mohd, Siti Munirah; Kamarudin, Shafinah; Ahmad, Azuan; Salleh, Rossly; Md Norwawi, Norita (Universitas Atma Jaya Yogyakarta, 2024)
Smart farming, one of the most rapidly growing technologies in the agriculture sector in the midst of the Industrial Revolution 4.0 era, signifies the integration of technologies into the industry. Numerous challenges in the agriculture sector were able to be decoded and formulated efficiently. Over the past few years, research on smart farming has grown expeditiously, observing every different cornerstone of the sector. This scoping review investigates the adoption of smart, addressing the critical issue of enhancing agricultural productivity and sustainability. The main objective of this study is to investigate the adoption of exogenous factors in smart farming technology through the lens of a scoping review, identifying the challenges faced by stakeholders. Selections of articles from several different sources published between 2010 and 2024 with specific keywords were thoroughly observed. Valuable information was identified and discussed, particularly the positive and negative factors influencing the adoption of smart farming. This study found that while smart farming technologies hold promises for the transformation of the agriculture field, widespread adoption is obstructed by technological, economic, and social barriers. The study contributes to the understanding of smart farming adoption and serves as a bedrock for an upcoming study in technology adoption, promoting efficient and sustainable agricultural practices.